Mesa redonda: Impacto de los avances en el conocimiento del Genoma humano - Castillo, Silvia; Cruz Coke, Ricardo; Allende R., Jorge; Valenzuela Y. , Carlos; Chomalí G., Padre Fernando (Revista Hospital Clínico Universidad de Chile, 2000)
Resumen no disponible